2006
DOI: 10.1300/j145v09n04_03
|View full text |Cite
|
Sign up to set email alerts
|

Educational Achievement in Adopted Children from China

Abstract: A sample of 77 adopted children from China and a matched sample of 77 Norwegian-born children were tested for educational achievement. The results did not show any significant differences between the two groups either in educational performance or in any other related areas. The findings are in contrast to other studies showing that international adoptees as a group have lower performance than non-adoptees. The study did show a greater disparity within the adopted group's performance compared to the Norwegian-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
2
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 41 publications
4
50
2
6
Order By: Relevance
“…Dalen and Rygvold reported that hyperactive behaviour was not more common in a study group of 77 adoptees from China than amongst non-adopted children [22]. Even if hyperactivity is not synonymous with ADHD, the findings illustrate that international adoptees are a heterogenous group and mental health outcomes may vary strongly between and within continents [23].…”
Section: Introductionmentioning
confidence: 78%
“…Dalen and Rygvold reported that hyperactive behaviour was not more common in a study group of 77 adoptees from China than amongst non-adopted children [22]. Even if hyperactivity is not synonymous with ADHD, the findings illustrate that international adoptees are a heterogenous group and mental health outcomes may vary strongly between and within continents [23].…”
Section: Introductionmentioning
confidence: 78%
“…Significant differences were therefore expected in studies in which behavioral issues of adoptees were compared with those of controls. The results from previous comparative studies conducted in community samples mainly led to the conclusion that significant differences were found between adoptees and control participants with regard to behavioral adjustment (Dalen & Rygvold, 2006;Dhavale, Bhagat, & Thakkar, 2005;Hawk & McCall, 2010). A meta-analysis of 98 adoptee-control studies concluded that adoptees displayed higher average levels of both externalizing and internalizing behavior than controls (Juffer & van IJzendoorn, 2005).…”
Section: Adopted Adolescents Follow a Different Pathway To Behavioralmentioning
confidence: 99%
“…Also, in comparison studies in which significant differences to the disadvantage of adoptees were found in behavioral adaptation, the effect sizes were low (Bimmel, Juffer, van Ijzendoorn, & BakermansKranenburg, 2003;Juffer & van IJzendoorn, 2005), suggesting first that variations in behavioral adjustment stay in the normal range (Dalen & Rygvold, 2006), and second that although adoptees display more behavior problems than their non-adopted counterparts, this concerns a minority of adoptees. The large majority function well, and much better than might be expected based on their background of deprivation (Juffer & van IJzendoorn, 2005).…”
Section: Adopted Adolescents Follow a Different Pathway To Behavioralmentioning
confidence: 99%
“…More recent studies continue to provide an optimistic outlook with fewer negative long term effects for children adopted from better quality Korean and Chinese orphanages (Dalen, 2002;Tan, Marfo & Dedrick, 2007. For example, South Korean-born children have shown the most promising educational outcomes (Dalen, 2002;Dalen & Rygvold, 2006;van Ijzendoorn, Juffer & Poelhuis 2005); children adopted from China as infants and toddlers acquire their "second-first language" rapidly Tan & Yang, 2005); and measures of Chinese girls' behavioural adjustment prior to the age of five show "comparable or even slightly better behavioural adjustment" to their non-adopted U.S. peers (Tan et al, 2010, p. 312).…”
Section: Pre-adoption Experiencesmentioning
confidence: 99%
“…However, the lack of accurate and available information about pre-adoption factors and the diversity of early experiences is problematic and therefore often precluded from the research (Dalen & Rygvold, 2006). When information is available, however, care must be taken not to over-pathologise these children based on their previous experience.…”
Section: Pre-adoption Experiencesmentioning
confidence: 99%